(untitled) (Olhares, 2020)
Modern dance and the art of eurythmy born at the beginning of the 20th century marked the beginning of a new approach in the language of movement and created conceptions about the body that dances, returning the gesture to the sacred place of ancient history. This break with the patterns established by the classical ballet sought to find again significant gestures for the dancing bodies and the narratives they wished to talk about themselves and the world in which they were inserted. Thus, it is intended to highlight the similarities and divergences of these two arts of the movement that were created at the beginning of modernity.